Solar Energy Applications in Houses, Smart Cities and Microgrids - Hernández-Callejo, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Five papers were selected for this Special Issue, with three relating to solar energy applications in houses, smart cities, and microgrids; one studying the relationship between the smart city model and the concept of energy sustainability; and one addressing the following two topics: the lack of effectiveness of detection algorithms based on the voltage/frequency displacement concept under voltage-controlled inverters and the applicability limits of others based on the impedance measurement (IM).